Treatment of arterial aneurysms of anterior cerebral circulation - Roganović Zoran (Vojnosanitetski Pregled, 2002)
Objectives: To analyze the outcome of either surgical or conservative treatment of patients with aneurysms on cerebral arteries. Design Retrospective study on 114 patients (89 operated and 25 not operated). Methods: Clinical state was graded from 0 to V, according to Hunt & Hess (HHG), and the treatment outcome was defined as favorable or poor, according to the modified Glasgow Outcome Score. The outcome was correlated with the type of treatment (operative or conservative), clinical state and aneurysmal localization. Results: Aneurysm was localized mostly on the anterior communicating (33.6%) and middle cerebral arteries (32.8%) and the patients were mostly in HHG II or III (34.4% and 25.2%). HHG after the aneurysmal rupture did not depend on the aneurysmal location (p>0.05). Favorable treatment outcome was noted: in 74.1% of all operated and in 60% of all conservatively treated patients (p>0.05)( in 81.6% of operated and in 33.3% of not operated patients with HHG=II-III (p<0.01)( in 78.8% of aneurysms of the middle cerebral artery and in 66.7% of those of the anterior communicating artery (p>0.05)( in 73.1% of patients with HHG=III and in 25% of patients with HHG=IV (p<0.01).Conclusions: Clinical state after the aneurysmal rupture did not depend on its localization. Results were better after the surgical, than after the conservative treatment. Outcome after the surgery depended on the clinical state of the patient, but not on the aneurysmal localization.